1989
DOI: 10.1029/jb094ib12p17619
|View full text |Cite
|
Sign up to set email alerts
|

Appalachian Stress Study: 3. Regional scale stress variations and their relation to structure and contemporary tectonics

Abstract: Using commercial hydrofracture data to supplement published stress data, we map regional variations in least horizontal stress magnitude (Sh) and orientation within the Paleozoic sediments of the Appalachian Plateau. Systematic trends revealed by the data are examined for correlations with structure (the study area includes a prominent salt detachment) and tectonic history. The dominant stress component present at all depths (including basement) throughout the region is ENE oriented compression and is most lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Extensive salt detachments often constitute stress discontinuity horizons (Davis & Engelder 1985): for example, Evans (1989) found a discontinuity in horizontal stress magnitude across the salinian salt of the Appalachian basin, and röckel and Lempp (2003) report a discontinuity in horizontal stress magnitude and direction at the Zechstein salt in the North German basin. It is thus of interest to compare Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive salt detachments often constitute stress discontinuity horizons (Davis & Engelder 1985): for example, Evans (1989) found a discontinuity in horizontal stress magnitude across the salinian salt of the Appalachian basin, and röckel and Lempp (2003) report a discontinuity in horizontal stress magnitude and direction at the Zechstein salt in the North German basin. It is thus of interest to compare Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In southeastern Canada and the northeastern United States the tangential stress due to rebound is subparallel to the regional ENE SHmax orientation, while the radial rebound stress is subparallel to S hmin. In a two-dimensional analysis of reboundrelated flexural stresses by Clark [1982], the ice sheet load was approximated as a right circular cylinder of paraboidal The rebound flexural stresses have been interpreted as sufficient to influence the stress field in the upper 1-2 km [Clark, 1982;Evans, 1989]. The potential perturbation at earthquake depths (typically 5-10 km in this region, Table 1) can be evaluated drawing on the analysis of frictional analysis presented above.…”
Section: Fault Plane Identification and Implications For The Nature Omentioning
confidence: 99%
“…The basin wide stress study indicated σ h /σ ν value of up to 0.7 in the corresponding depth at this well location [26]. With the vertical stress of 54 MPa from Table 1, the upper bound minimum horizontal stress will be 37.8 MPa.…”
Section: Pr-ga-ann Methodsmentioning
confidence: 99%
“…Table 3 shows the comparison of the PR-GA-ANN based inverse analysis results of geomechanical properties and horizontal in-situ stresses with the field observation or reports of the area for the well MIP 3H. The basin wide stress study indicated σh/σν value of up to 0.7 in the corresponding depth at this well location [26]. With the vertical stress of 54 MPa from Table 1, the upper bound minimum horizontal stress will be 37.8 MPa.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation